Research and Implementation of an AI-Based Human Posture Recognition System - Miao, Feng; Zhang, Qiang; Yan, Jun (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
This study aims to construct a human posture recognition system based on artificial intelligence, with the goal of enhancing the accuracy and real-time performance of posture recognition. The system adopts a modular design that encompasses data collection, preprocessing, feature extraction, posture recognition, and result evaluation. By integrating multi-source data through a fusion strategy that combines visual and inertial sensor data, the system utilizes deep learning algorithms to achieve precise posture recognition. Experimental results demonstrate that the system excels in both sports training and medical rehabilitation fields. It can provide personalized training recommendations for athletes and assist coaches in optimizing training programs. Additionally, it helps doctors and therapists accurately monitor patient recovery progress, thereby improving rehabilitation outcomes. In the future, continuous optimization of the system will be pursued, expanding its application domains and providing stronger technical support for the intelligent development of related industries.